Predictive Value of HE4 in Platinum-Based Chemotherapy for Ovarian Cancer: A Systematic Review - Han, Yue; Jiang, Lili; Liu, Kuiran; Ouyang, Ling; Li, Yan (Frontiers in Oncology, 2021)
Objective: To evaluate the value of serum Human epididymis protein 4 (HE4) for predicting the resistance of ovarian cancer (OS) to platinum chemotherapy. Method: We searched the MEDLINE (PubMed), EMBASE, Cochrane Central, Web of Science, SCOPUS, and CNKI databases and screened all studies evaluating serum HE4 for predicting OC resistance to treatment with platinum. Two researchers independently evaluated the quality of all eligible original studies using QUADAS-2. RevMan 5.4 was used to compile the quality evaluation form. We also performed a meta-analysis with STATA15.1, and Deek’s funnel plots were used to detect any publication bias. Results: Eight studies were included in the final meta-analysis. Our results showed that the sensitivity and specificity of preoperative serum HE4 in predicting the resistance of OC to platinum chemotherapy was 80% and 67%, respectively. The diagnostic odds ratio was 8, and the AUC was 0.78 (95% CI: 0.75-0.82), whereas the pooled sensitivity and specificity of serum HE4 after the third-cycle of chemotherapies for predicting chemoresistance in OC was 86% and 85%, respectively, with a diagnostic odds ratio of 33 and AUC = 0.92 (95% CI: 0.89 – 0.94). Conclusion: HE4 may be an effective predictor of platinum-based chemotherapeutic resistance of OC. Serum HE4 levels after the third chemotherapy cycle may be indicative for clinical practice. Further research is needed to validate the significance of HE4 in the long-term management of OC.